Lung rehabilitation in stable chronic pulmonary obstructive disease - Portugal Vivanco, José (2009)
Lung rehabilitation in chronic obstructive pulmonary disease (COPD) is a tangible fact supported by scientific evidence. Nowadays it is clearly recognized that there is dyspnea reduction, an increase in exercise capacity, better quality of life, and less use of healthcare services in COPD patients undergoing lung rehabilitation programs.